Determining the effects of tryptophan:lysine ratio in diets containing dried distillers grains with solubles on growth performance of finishing pigs - Nitikanchana, S.; Usry, J.L.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,235 pigs (PIC 1050 × 337; initially 149 lb) were used in a 71-d study to determine the effects of tryptophan:lysine ratio in diets containing 0, 20, or 40% dried distillers grains with solubles (DDGS) on growth performance of finishing pigs raised in a commercial environment. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 6 dietary treatments in a completely randomized design with 26 to 28 pigs per pen and 7 to 8 replications per treatment. Treatments were arranged as a 2 × 3 factorial with main effects of standardized ileal digestible (SID) tryptophan:lysine ratio (16.5 or 20% of lysine) and DDGS (0, 20, or 40%). Overall (d 0 to d 71), no differences occurred in growth performance due to SID tryptophan:lysine ratio. Increasing DDGS resulted in poorer F/G (linear, P = 0.02), but did not influence other growth performance criteria. For carcass characteristics, increasing the SID tryptophan:lysine ratio increased (P = 0.02) carcass yield percentage with the greatest improvement in yield observed when diets contained high levels (20 and 40%) of DDGS (tryptophan × DDGS interaction, P = 0.07). Pigs fed high levels of DDGS had reduced loin depth (linear, P = 0.02); however, the lowest loin depth was at 40% DDGS for 16.5% SID tryptophan:lysine ratio and at 20% DDGS for 20% SID tryptophan:lysine ratio resulting in a tryptophan × DDGS interaction (quadratic, P = 0.02). A tendency of tryptophan × DDGS interaction (linear, P = 0.08) was observed for lean percentage, with lean percentage decreasing as DDGS increased in diets containing the 16.5% SID tryptophan:lysine ratio and no change in lean percentage as DDGS increased in diets containing the 20% SID tryptophan:lysine ratio. The tendency of interactions for yield and lean percentage indicate an advantage to increasing the SID tryptophan:lysine ratio in diets with high levels of DDGS, but no effects on growth performance were observed due to SID tryptophan:lysine ratio.
Keywords: Swine; Amino acid ratio; DDGS; Lysine; Tryptophan; Finishing pig